“JOHN THE FORERUNNER OF SLAVONIC ARCHAEOLOGY AND FOLKLORISTICS”: IVAN FRANKO’S RECEPTION OF ZORIAN DOLENHA-KHODAKOVSKYI - Pylypchuk, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights Franko’s reception of Zorian Dolenha-Khodakovskyi’s folkloristic and ethnographic legacy. It has been emphasized that the author of “The Studies on Ukrainian Folk Songs” systematically resorted to the handwritten materials of the Polish amateur folklorist to include them as illustrations in his own research, and moreover highly appreciated indefatigable collecting efforts of the scholar and remarked his audacity and originality in the comments on oral lore samples, in particular in his «O Słowiańszczyźnie pred chrześciaństwem».